Ratios of monocytes and neutrophils to lymphocytes in the blood predict benefit of CDK4/6 inhibitor treatment in metastatic breast cancer - Stefanos Ioannis Moukas; Sabine Kasimir-Bauer; Mitra Tewes; Hans-Christian Kolberg; Oliver Hoffmann; Rainer Kimmig; Corinna Keup (Scientific Reports, 2023)
Abstract Biomarkers to identify metastatic breast cancer (mBC) patients resistant to CDK4/6 inhibition (CDK4/6i) are currently missing. We evaluated the usefulness of the monocyte-to-lymphocyte ratio (MLR), the neutrophil–to-lymphocyte ratio (NLR) and the platelet-to-lymphocyte ratio (PLR) as predictive markers for de novo resistance to CDK4/6i. Various blood cell counts and MLR, NLR, PLR were recorded before treatment initiation (baseline) and four weeks later from 97 mBC patients receiving endocrine therapy (ET) alone or in combination with CDK4/6i. Binary blood cell count/ratios (mean = cut-off) were related to outcome using Cox regression. High MLR (p = 0.001) and high NLR (p = 0.01) at baseline significantly correlated with a shorter progression-free survival (PFS) in the CDK4/6i cohort, independent of any other clinical parameter as determined by multivariate Cox regression. Both, high MLR (p = 0.008) and high NLR (p = 0.043) as well as a decrease in PLR after four weeks of CDK4/6i first line treatment (p = 0.01) indicated a shorter overall survival. Moreover, decreasing PLR (p = 0.043) and increasing mean corpuscular volume (MCV; p = 0.011) within the first cycle of CDK4/6i correlated with a shorter PFS and decreasing MLR (p = 0.039) within the first cycle of first-line CDK4/6i was also correlated with shorter PFS. In summary, easily assessable blood cell parameter were shown to have predictive, monitoring and prognostic value and thus, could, in future, be used for individualized CDK4/6i therapy management. Most importantly, the imbalance of NLR and MLR at baseline might serve as predictive marker for de novo resistance to CDK4/6i in mBC patients.